2023
DOI: 10.1039/d2ta08915g
|View full text |Cite
|
Sign up to set email alerts
|

Designed sulfonate-based covalent organic frameworks with dual functions of recognition and encapsulation

Abstract: Seeking for novel materials with simultaneous task-specific recognition and enrichment for trace pollutants is of great significance for the environmental security. Here, we developed a sulfonate-based covalent organic framework (sCOF)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The existence of a sharp, intense diffraction peak at 5.1° indicated the high crystallinity of COF-I, which is representative of the (100) plane in this new hexagonal olefin-linked 2D COF. To deduce the structure and the configuration of the layers in COF-I, we performed atomistic simulations (Figure b). Following the previously introduced parametrization approach and studies and utilizing the Tinker code, we parametrized a force field using quantum-mechanical (QM) reference data (BLYP+D3/cc-pVDZ). By using these interatomic potentials to optimize both the geometry of the COF and the cell parameters and systematically varying the interlayer arrangement, we could discriminate the three-dimensional structures energetically. These atomistic simulations revealed that, for the solvent-free structure, the energetically most preferred structure is a highly dense slipped layer stacking, which increases the interaction between the layers.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of a sharp, intense diffraction peak at 5.1° indicated the high crystallinity of COF-I, which is representative of the (100) plane in this new hexagonal olefin-linked 2D COF. To deduce the structure and the configuration of the layers in COF-I, we performed atomistic simulations (Figure b). Following the previously introduced parametrization approach and studies and utilizing the Tinker code, we parametrized a force field using quantum-mechanical (QM) reference data (BLYP+D3/cc-pVDZ). By using these interatomic potentials to optimize both the geometry of the COF and the cell parameters and systematically varying the interlayer arrangement, we could discriminate the three-dimensional structures energetically. These atomistic simulations revealed that, for the solvent-free structure, the energetically most preferred structure is a highly dense slipped layer stacking, which increases the interaction between the layers.…”
Section: Resultsmentioning
confidence: 99%
“…Covalent organic framework (COF), formed by linking organic building blocks through covalent bonds, has been regarded as an ideal material for ion transport/separation due to its intrinsic attributes, including high specific surface area, regular, and periodically arranged pore structure. , Two-dimensional (2D) COF material shows great potential in ionic transport due to its periodic columnar π array and uniform one-dimensional nanopore. , The shuttle effect of polysulfide for Li–S battery could be effectively suppressed through the uniform microporous structure and rich polar groups of COF. Particularly, the regular and unambiguous porous structure of COF could serve as the ideal material for exploring fundamental Li + transfer mechanism and facilitating Li + conduction. , Recently, Jeong et al . reported a lithium sulfonated COF (TpPa-SO 3 Li) conductor, which realized an ionic conductivity of 2.7 × 10 –5 S cm –1 at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Twodimensional (2D) COF material shows great potential in ionic transport due to its periodic columnar π array and uniform one-dimensional nanopore. 25,26 The shuttle effect of polysulfide for Li−S battery could be effectively suppressed through the uniform microporous structure and rich polar groups of COF. 27−29 Particularly, the regular and unambiguous porous structure of COF could serve as the ideal material for exploring fundamental Li + transfer mechanism and facilitating Li + conduction.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Therefore, COFs have great potential for uorescence sensing. [38][39][40] In addition, COFs not only have adjustable structure, pore size and functional groups, 41,42 but also have adjustable uorescence properties. For example, Li et al achieved the adjustable emission colors of COFs from blue to yellow or even white by changing the size of conjugated connectives and side chains.…”
Section: Introductionmentioning
confidence: 99%